Hubungan Antara Kepemimpinan Transformasional Kepala Sekolah Dan Kecerdasan Emosional Dengan Kepuasan Kerja Guru SMP Negeri 1 Sagaranten - Eti Robiatul Adawiah; Kun Nurachadijat (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research was conducted to study the relationship between school principals' transformational leadership and emotional intelligence with teacher job satisfaction. The methods used are surveys and data analysis techniques using simple correlation statistical tests and multiple correlations as well as simple linear regression tests, multiple linear regression tests and partial correlation tests. The results of the study yielded three conclusions: first, there was a very significant positive relationship between the situational leadership of the school principal (X1) and teacher job satisfaction (Y). Second, there is a very significant positive relationship between Emotional Intelligence Variable (X2) and Teacher Job Satisfaction (Y). Third, there is a very significant positive relationship between the Principal Transformational Leadership (X1) and Emotional Intelligence (X2) variables together with Teacher Job Satisfaction (Y). Based on these things it can be concluded that teacher job satisfaction can be increased through the principal's Transformational leadership and Emotional Intelligence.